Real-time measurement of non-lethal platelet thromboembolic responses in the anaesthetized mouse - Tymvios, Charalambos; Jones, Sarah; Moore, Christopher; Pitchford, Simon C; Page, Clive P; Emerson, Michael (Thrombosis and haemostasis, 2008)
Identifying and evaluating new therapeutic targets in platelets requires advanced animal models in which platelet responses can be measured directly and in situ. This is important because platelet function is strongly influenced by external factors such as those originating from the vascular endothelium. Our objectives were to record graded, non-lethal thromboembolic platelet responses to platelet agonists in situ in the mouse and to demonstrate an inhibitory effect of aspirin in our model. Radiolabelled platelets were infused into anaesthetized mice and responses to ADP, collagen and thrombin measured as changes in platelet associated counts in miniaturized detection probes placed over the thoracic region. All agonists induced dose-dependent changes in platelet counts due to accumulation of thrombi in the pulmonary vasculature. We confirmed a specific platelet effect by comparing platelet and erythrocyte responses and showing platelet aggregates in the lung vasculature histologically. Simultaneous injection of collagen and adrenaline induced increased and protracted synergistic platelet responses compared with individual injection of these agents and aspirin inhibited collagen-induced responses. We confirmed the clinical relevance of our model by showing that platelet thromboembolism in the mouse, like pulmonary embolism in humans, impaired cardiovascular performance. We present a refined method for measuring platelet agonist dose-responses and thromboembolism in real-time without inducing mortality in the mouse. Our technique will be useful in investigating the molecular determinants of physiological and pathophysiological platelet function in an in-vivo context and will enable investigations of both platelet and non-platelets mediators of thrombus formation.